(untitled) - International Conference on Business History (Tokyo, 1986)
This book introduce prerequisites for the development of managerial capitalism. Managers, families and fiananciers. The rise of the managerial enterprise in Germany. Strategy, structure, and management development in the United States and Britain....
Keywords: Quản trị công nghiệp,Industrial management; Lịch sử,Hội nghi,History,Congresses